2016
DOI: 10.5152/balkanmedj.2016.16383
|View full text |Cite
|
Sign up to set email alerts
|

A Comparision of the Effect of Sugammadex on the Recovery Period and Postoperative Residual Block in Young Elderly and Middle-Aged Elderly Patients

Abstract: Background:The importance of the characteristics of anesthesia and postoperative residual curarization (PORC) in the elderly population should be a growing concern in this century. Aims: To investigate the effect of sugammadex on the duration of the recovery from neuromuscular blocking agents and postoperative residual curarization in the young elderly and middle-aged elderly patients who underwent elective laparoscopic cholecystectomy, followed by a train of four (TOF) watch monitorization. Study Design: Pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…This result was attributed to decreased circulatory system dynamics, and the resulting delay in drug distribution present in elderly people. Similar conclusions were reached by Suzuki et al [8] who compared the return period for muscle strength after using sugammadex in patients between 20 and 50 years of age, as well as those older than 70, and Turkish authors who assessed the effect of age on muscle strength return after using sugammadex in patients between 65 and 74, as well as those older than 75 years of age [9]. In all of the cited articles, age did not affect the presence of side effects, while the medication was considered to be well-tolerated.…”
supporting
confidence: 62%
“…This result was attributed to decreased circulatory system dynamics, and the resulting delay in drug distribution present in elderly people. Similar conclusions were reached by Suzuki et al [8] who compared the return period for muscle strength after using sugammadex in patients between 20 and 50 years of age, as well as those older than 70, and Turkish authors who assessed the effect of age on muscle strength return after using sugammadex in patients between 65 and 74, as well as those older than 75 years of age [9]. In all of the cited articles, age did not affect the presence of side effects, while the medication was considered to be well-tolerated.…”
supporting
confidence: 62%
“…41,47e49,51,53,56e58,63 Some studies did not specify the measurement time point at the PACU at all. 55 Globally considered, 84 of the 109 included study arms (77%) reported PORC based on TOFRs measured at the PACU. 9e13,17e26, 28,30e33,33,38,39,41,43e46,49,51e53,55e58,61,63 Additional intra-study heterogeneity is introduced by the fact that measurements after PACU arrival were not consistently standardised.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a prospective clinical trial, Yazar et al investigated the effect of sugammadex 2 mg/kg on duration of recovery from moderate rocuronium-induced NMB in elderly patients undergoing sevoflurane anesthesia. 44 They found that the median (range) time from T 2 to TOF ratio of 0.9 with sugammadex was 3.27 (1.41–5.37) minutes in younger elderly adults (aged 65–74 years) and 5.5 (2.47–9.54) minutes in older elderly patients (aged ≥75 years) ( P <0.001). 44 …”
Section: Pharmacology In the Elderlymentioning
confidence: 97%
“… 44 They found that the median (range) time from T 2 to TOF ratio of 0.9 with sugammadex was 3.27 (1.41–5.37) minutes in younger elderly adults (aged 65–74 years) and 5.5 (2.47–9.54) minutes in older elderly patients (aged ≥75 years) ( P <0.001). 44 …”
Section: Pharmacology In the Elderlymentioning
confidence: 97%
See 1 more Smart Citation